Signs of illness, treatment, and support for young children in Guinea: A prospective community study - Gordon, Andrew J.; Yoder, P. Stanley; Camara, Mamadou (DHS Qualitative Research Studies No. 9., 2004)
This prospective study of childhood illness was undertaken to examine how childhood illnesses are recognized and treated by Maninka-speaking mothers and others in central Guinea. By making daily visits to households with more than 150 children five years old and younger over a period of two months, and talking with mothers and others about their children, field workers were able to follow children as their health status changed, noting what was done by whom to improve the child's health. The study found that mothers with strong social relations to their husband's family responded more quickly to illness in their children.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This report presents findings from a qualitative research study conducted in Guinea in 2001–2003 as part of the MEASURE DHS+ project. It was carried out under the direction of the Department of Anthropology, University of Houston and ORC Macro. Funding was provided by the U.S. Agency for International Development (USAID). Additional information about the DHS project may be obtained from ORC Macro, 11785 Beltsville Drive, Calverton, MD 20705; Telephone: 301-572-0200, Fax: 301-572-0999, Internet: www.measuredhs.com. This publication was made possible through support provided by the U.S. Agency for International Development under the terms of Contract No. HRN-C-00-97-00019-00. The opinions expressed herein are those of the authors and do not necessarily reflect the views of the U.S. Agency for International Development.